Diagnostic procedure in patients with neoplasm and malignant pleural effusion – our experience - Kacprzak, Grzegorz; Bobek, Vladimir; Pawełczyk, Konrad; Kolodziej, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction: Malignant pleural effusion (MPE) is a serious diagnostic problem. The proper diagnosis of the cause of the effusion allows the appropriate treatment to be applied. The aim of this study was to assess the usefulness of diagnostic procedures in patients with MPE. Material and methods : Between January 1996 and June 2008, 237 patients (ages 23-84) were diagnosed with and treated for MPE in the Department of Thoracic Surgery. They belonged to the following groups: Group I: 121 (51.1%) patients with a previously diagnosed neoplasm, when the MPE occurred in the course of disease; 116 (48.9%) patients required invasive diagnostic methods, because of the lack of a clearly established cause of pleural effusion. These patients underwent either thoracoscopy (videothoracoscopy) (group II, n = 108) or diagnostic thoracotomy (group III, n = 8). Results : There were 65 patients with lung cancer, 26 with breast cancer, 6 with ovarian cancer, 6 with lymphoma or Hodgkin’s disease, 1 with mesothelioma pleurae, and 17 with other malignancies in group I. Neoplastic cells in pleural effusion were diagnosed in 66 (54.5%) patients. From among 108 patients (group II) who underwent thoracoscopy (videothoracoscopy), malignancies were diagnosed in 107 (99.1%) of them. In 1 patient the malignancy was diagnosed in a later period. In 5 patients with diagnosed adenocarcinoma the primary focus was not established. In all patients who underwent diagnostic thoracotomy (group III) malignancy was established. There were 2 patients with lung cancer, 4 with mesothelioma pleurae, 1 with metastases of melanoma, and 1 with an unknown primary tumor. Conclusions: Examination of the neoplastic cells in pleural effusion is a valuable element in diagnosis of MPE. Thoracoscopy (videothoracoscopy) is the essential invasive diagnostic procedure in the case of suspicion of neoplastic disease with malignant pleural effusion.